GAMBARAN TINGKAT KECEMASAN KELUARGA DENGAN SALAH SATU ANGGOTA KELUARGANYA MENDERITA SKIZOFRENIA DI POLIKLINIK JIWA RUMAH SAKIT JIWA PROVINSI BALI TAHUN 2012 - I Wayan Aryo Rumambi Kristian; I Nengah Sumirta; I Ketut Suarnata; Ni Made Sri Muryani (Jurnal Kesehatan Medika Udayana, 2019)
Background: The presence of schizophrenia in the family is a very heavy stressor that must be borne by the family. Families who have family members with schizophrenia can increase stress and family anxiety. The purpose of this study was to describe the level of anxiety of families with one of their family members suffering from schizophrenia at Poliklinik Jiwa Rumah Sakit Jiwa Provinsi Bali. Method: This research is a quantitative research with descriptive research design with consecutive sampling technique, with a sample of 30 respondents. Results: Most of the families of schizophrenia patients experienced mild anxiety levels of 12 (40.0%) respondents, moderate anxiety as many as 11 (36.7%) respondents, severe anxiety as many as 6 (20.0%) respondents, and panic was experienced by 1 (3.3%) respondents. Conclusion: Most of the families of schizophrenic patients experience mild anxiety, as many as 12 with symptoms often feeling lethargic, muscle twitch, tremor, and often feeling short of breath.Key words: Family; Anxiety; Skizofrenia